Equipment to determine storage times of modified asphalts at critical conditions - Villegas Villegas, Rafael Ernesto (2021)
This paper attempts to design a storage tank sized for laboratory use, aiming to study the stability of modified asphalt during storage. The tank design seeks to maintain similar dimensions to those of industrial tanks for asphalt storage. Also, it aims to promote phase separation to analyze the storage under critical conditions. For this reason, this research carries out a comparison of commercially available tanks and their dimensional ratios, as well as studying the theories of sedimentation and phase separation. The main objective of this document is to provide a mechanical design of a storage tank that can be manufactured with accessible materials, which allow to perform the necessary sampling to examine the stability of modified asphalt under critical conditions of storage. In addition, the document establishes bases for the approach of a model that contributes to the determination of maximum storage time. It pretends to verify the quality of the modified asphalt design.